A self-destructive nanosweeper that captures and clears amyloid β-peptides - Qiang Luo (Nature Portfolio, 2018)
Cerebral amyloid β-peptide accumulation is a causative factor in Alzheimer’s Disease. Here the authors design a 'nanosweeper' that binds amyloid β-peptide and induces autophagy to clear the accumulated plagues.